2020
DOI: 10.1002/aisy.202000198
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Deep Learning Spectroscopy of Scalogram Infused CNN Classifiers for Robust Identification of Post‐Hypoxic Epileptiform EEG Spikes

Abstract: Hypoxic-ischemic (HI) insults before and during birth, secondary to events such as placental abruption or umbilical cord occlusion, are a significant contributor to neonatal brain injury (hypoxic-ischemic encephalopathy; HIE). [1,2] The preterm newborn is at greater risk of HIE. [1] In contrast to an overall incidence of 1-3/1000 live births at term in high-income countries, preterm babies born before 37 weeks have an HIE incidence of around 37.3/1000 babies born before 37 weeks of gestation, rising to an over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…Meanwhile, the most commonly adopted feature that is widely implemented in EEG signal characterization includes timedomain (TD), time-frequency domain (TFD), frequency domain (FD), fourier transform (FT), discrete wavelet transform (DWT), and continuous wavelet transform (CWT)-based features [30]. Abbasi models to detect HI brain injury and got satisfactory results [31]. Logesparan et al [32] used various statistical feature extraction methods on EEG datasets but concentrated on only two features, "relative power" and "line length," which produced better performance in seizure detection.…”
Section: Feature Extraction and Selection Techniques Applied Inmentioning
confidence: 99%
“…Meanwhile, the most commonly adopted feature that is widely implemented in EEG signal characterization includes timedomain (TD), time-frequency domain (TFD), frequency domain (FD), fourier transform (FT), discrete wavelet transform (DWT), and continuous wavelet transform (CWT)-based features [30]. Abbasi models to detect HI brain injury and got satisfactory results [31]. Logesparan et al [32] used various statistical feature extraction methods on EEG datasets but concentrated on only two features, "relative power" and "line length," which produced better performance in seizure detection.…”
Section: Feature Extraction and Selection Techniques Applied Inmentioning
confidence: 99%
“…We have previously shown that micro-scale sharp-wave EEG patterns with amplitudes between 20-80 µV and a duration between 70 and 250 ms (frequency range: 4 to 14.3 Hz, in the θ (4-8 Hz), α (8-12 Hz), and lower-beta β band (i.e., 12-14.3 Hz)) were superimposed on a suppressed EEG background, within the latent phase of fetal sheep data (103 ± 1 days, human brain maturation equivalent ~28-30 weeks) which are a reliable marker for hypoxic-ischemic encephalopathy (HIE) (see Figure 1c,d) [6,15]. We have shown that EEG sharp-waves can help to predict the latent phase of injury after an HI insult, where a larger number of sharp-waves within the first 30 min post-HI is associated with greater subcortical neuronal survival in the caudate nucleus (r = 0.80).…”
Section: Micro-scale Sharp-wave Eeg Waveforms-an Hi Biomarkermentioning
confidence: 99%
“…Our team has previously shown that in preterm fetal sheep these EEG waveforms emerge in the form of micro-scale sharp-waves and gamma spike transients, and that they are significantly correlated with the subcortical brain damage post HI injury [6,15]. Our team has successfully developed and validated automated advanced signal processing technology, based on deep-learning, for the identification, quantification, and localization of these patterns in preterm fetal sheep data (accuracy > 99%) [15,16]. We have previously shown that micro-scale sharp-waves, in particular, contain timing information related to the evolution of injury in the latent phase after HI.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, and crucially, the non-linear transformations implemented by the multiple layers of the deep neural networks can extract low-level features that make preprocessing unnecessary. This makes this approach a very suitable tool for classification and regression tasks applied to EEG signals [1,[38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%